Analysis of Corporate Entrepreneurial In PT. Bank X - Saputra, Muhammad Pittrawan; Rudito, Bambang (Journal of Business and Management, 2012)
One of the significant way to improve the perfomance of the company is developing corporate entrepreneurship within the employees. An Entrepreneurial mindset is needed in this growing business world. Therefore, for having a good organization performance, a company also has to have entrepreneurial leaders. The author decided to measure and analyze the corporate entrepreneurial in PT. Bank X as this company is one of the biggest bank in Indonesia that very influential to the economic performance of Indonesia.author use Entrepreneurial Orientation Survey (EOS) and Entrepreneurial Leadership Questionaire (ELQ) to measure the corporate entrepreneurial culture and leadership characteristic within directorates in PT. Bank X.[1]Purpose:this research is conducted to analyze the entrepreneurial orientation (dimensions of entrepreneurship culture) and analyze the importance of entrepreneurial leadership characteristics.Design/methodology/approach:author use Entrepreneurial Orientation Survey (EOS) and Entrepreneurial Leadership Questionaire (ELQ) to measure the corporate entrepreneurial culture and leadership characteristic inPT. Bank X within the directorates.Findings:Using those three kinds of approaches, author will find the entrepreneurhip orientation implemented by employees of the directorate. And also this research finds the leadership characteristic of directorates.Research limitations/implications: This research is focuses on orientation of the employee and the leaders’ characteristic.Originality/value:This research paper contains about measuring entrepreneurial culture of PT. Bank X where developing corporate entrepreneurial within the company is a significant way to improve the company performance.Keywords: entrepreneurship, intraprneurship, EOS, ELQ.Category: Corporate Entrepreneurship